Rubus adenotrichus fruit extracts phytochemical characterization and antioxidant power evaluation for dermocosmetic formulations - Madrigal Redondo, German (2017)
There are more than 700 species of the genus Rubus, popularly known as Mora (tropical highland blackberry). In Costa Rica, the species Rubus adenotrichus has been characterized by its high content of antioxidant substances, becoming one of the most cultivated species and that may have characteristics to be used in cosmetics or medicine. The objective of the present study is to identify the main phytochemical groups and to quantify the main markers in order to associate them with cosmetic or medicinal functions in pharmaceutical products. Ripe fruits of Rubus adenotrichius were fractionated with solvents of low, medium and high polarity, followed by a phytochemical screening according to the World Health Organization Guidelines for the Control of Quality of Products of Natural Origin. The antioxidant properties were evaluated by means of the H-ORAC and DPPH test; the concentration of total phenols by Folin-Ciocalteau and antocinanins by differential pH was determined. Finally, the physicochemical properties of the aqueous extract, such as pH, specific gravity, Brix grades, conductivity, and osmolarity was determined and an absorption spectrum from 260 to 700 nm was obtained. Phenolic compounds were found as condensed and non-condensed tannins, anthocyanins, flavonoids, terpenes, and alkaloids as major phytochemical groups, a high antioxidant power measured in H-ORAC 311 ± 7.63 μg/mol Trolox Equivalent/g of dry fruit, and EC 50 118.46 mg/L for the aqueous extract. The total phenols found was 20.85 ± 0.27 mg/g of dry sample of gallic acid equivalents which makes the Rubus adenotrichus fruit an excellent component for bacteriostatic, anti-aging, anti-wrinkle, nourishing and moisturizing formulations, and the astringent effect also allows its application to small superficial wounds on the skin. Likewise, the acidic pH of 3.55 ± 0.1 is beneficial for maintaining the cutaneous acid mantle thereby favoring the normal flora of the skin, but may be a problem for the formulation of carbomer-based gels or the incorporation of preservatives. The aqueous extract is hyperosmotic (559.66 ± 3.21 mOs/kg) and has a high electrical conductivity (285 ± 2 μS/cm) due to the presence of electrolytes and a considerable amount of sugars, according to Brix degrees (7.543° ± 0.005°). Finally, the 4% w/w aqueous extract shows an absorption of ultraviolet radiation of 25% in the wavelengths from 260 to 400nm, by which it also could be useful for formulating compositions for sun protection.